Pengaruh Likuiditas, Kapitalisasi Pasar, Book to Market, Pertumbuhan Aset, Profitabilitas dan Kebijakan Dividen terhadap Return Saham: Bahasa Indonesia - Yenny Setiawaty; Barlia Annis Syahzuni (Jurnal Riset Akuntansi Politala, 2026)
Changes in stock prices between the purchase price and the price after a certain period will affect the amount of profit or loss obtained from stock investments. This study aims to provide empirical evidence regarding the relationship between liquidity, market capitalization, book-to-market, asset growth, profitability, and dividend policy on stock returns. The study was conducted using panel data regression on 28 energy sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2022-2024. Statistical analysis was applied using a Fixed Effect Model selected through the Chow and Hausman tests. The selected model met the classical assumption test. Data processing results show that liquidity, market capitalization, book-to-market, asset growth, profitability, and dividend policy simultaneously influence stock returns. Meanwhile, the results of testing the influence of these variables on stock returns partially show that profitability has a significant positive effect, while market capitalization and asset growth have a significant negative effect. However, liquidity, book-to-market, and dividend policy have no significant effect. Future studies are recommended to use the firm value variable because companies capable of creating good value will be responded positively by the market through increased stock prices and increased returns for investors.